Proper absolute extensor
We describe the proper absolute (neighborhood) extensors for the class of at most n-dimensional spaces, notation A(N) E_p (n). For example, the unique locally compact n-dimensional separable metric space X AE_p (n) satisfiyng the DD^n P-property is the space obtained by deleting a point from the n-dimensional Menger compactum. Non-metrizable A(N) E_p (n)-spaces are also described. , journal=Topology Proceedings, author=Valov, Vesko, year=2023, month=Aug., pages=107–115